2016
DOI: 10.1002/srin.201500404
|View full text |Cite
|
Sign up to set email alerts
|

Induction Heat Treatment of Sheet‐Bulk Metal‐Formed Parts Assisted by Water–Air Spray Cooling

Abstract: In order to produce components with massive secondary functional elements from sheet metal bulk forming operations, termed sheet-bulk metal forming, can be applied. Owing to high, three-dimensional stress and strain states present during sheet-bulk metal forming, ductile damage occurs in the form of micro-voids. Depending on the material flow properties, tensile residual stresses can also be present in the components' formed functional elements. During service, the components are subjected to cyclic loading vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The spray cooling rate must be dynamically controlled to maintain competitiveness and continuously produce high-strength, high-quality steel at the highest productivity during continuous casting. Besserer et al [13] adopt orbital forming method to manufacture semi-finished parts which are used DP600 deep-drawing steel as the material, and perform surface heat treatment on parts. The results showed that a proper water-air spray cooling process could induce compressive stresses which is conductive to improve fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…The spray cooling rate must be dynamically controlled to maintain competitiveness and continuously produce high-strength, high-quality steel at the highest productivity during continuous casting. Besserer et al [13] adopt orbital forming method to manufacture semi-finished parts which are used DP600 deep-drawing steel as the material, and perform surface heat treatment on parts. The results showed that a proper water-air spray cooling process could induce compressive stresses which is conductive to improve fatigue life.…”
Section: Introductionmentioning
confidence: 99%